Updated basic prosthodontics terms glossary. English-Spanish. - Betancourt García, Ana Ibis (2022)
Dentistry as a branch of Medical Sciences is influenced by a great deal of scientific information written in English, compelling the dental professionals to be updated in English language for a better science understanding. One of the means and methods to fulfill such goal is through English terms glossaries in which in a very simple way provide the meaning of the most frequent and important words of a certain area of knowledge. This Glossary focused on Prosthodontics has been conceived mainly as a working and reference tool for dental students and post- graduated professionals, gathering almost 150 english terms focused on that branch of dentistry. Some terms have been left out of the Glossary because of their similarity to the Spanish equivalent. However, others were included because of their special translation. It is not an attempt to give all the words and phrases related to dental prosthesis; the aim is only to offer a quick and an updated reference on the most common and indispensable terms in this field.